Tinjauan Komparatif Potensi dan Efikasi Medan Elektromagnetik Extremely Low Frequency (ELF) dalam Mendukung Kesehatan dan Regenerasi Tulang - Sabda Dwi Arvinda; Rayhan Al-Hayubi; Nazwa Amelia Purnama; Ardian Sah; Diyajeng Luluk Karlina (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Bone health is a vital element in the quality of life aspect, especially with the increasing risk of osteoporosis and fractures with age. Extremely Low Frequency (ELF) electromagnetic field therapy offers the potential for bone regeneration through collagen synthesis, osteoblast stimulation, and molecular signal modulation. This study evaluates the potential and efficacy of ELF for bone health based on scientific literature. The results of the analysis show that ELF is effective in accelerating healing, increasing bone density, and is safe at certain intensities. However, optimization of parameters such as duration and intensity of exposure is still needed. This study supports the development of standard protocols for safe and effective ELF applications in bone therapy.